Surgical Management of Primary Skull Base Osteosarcomas: Impact of Margin Status and Patterns of Relapse. Issue 1 (12th September 2019) - Raza, Shaan M; Habib, Ahmed; Wang, Wei-Lien; Gildey, Paul W; Conley, Anthony P; Nader, Marc-Elie; Hanna, Ehab Y; Su, Shirley Y; DeMonte, Franco
Abstract: BACKGROUND: Skull base osteosarcomas are aggressive neoplasms characterized by bony invasion and extracompartmental/extra-osseous soft tissue extension that pose obstacles to achieving complete resection. Management is further complicated by the paucity of data regarding the efficacy of surgery within the treatment paradigm. OBJECTIVE: To identify the impact of margin status on local progression free survival (PFS) and disease specific survival (DSS). METHODS: A retrospective review was performed of 36 patients with osteosarcoma who underwent gross total resection with negative margins (R0), or positive margins (R1). Patient demographics, prior treatments, relapse patterns, and survival were collected. Univariate analysis was performed to determine the impact of margin status on the PFS (primary outcome) and DSS (secondary outcome). RESULTS: R0 resection was achieved in 67%, 25% patients had local recurrence, and 19.4% patients had distant metastasis. In assessing the entire cohort, R0 resections had improved DSS ( P  = .002) and PFS ( P  = .04). In chemotherapy-naïve patients, R0 resections also had improved impact on PFS ( P  = .04) and DSS ( P  = .027). For radiation-naïve patients, improvements in PFS ( P  = .026) and DSS ( P  = .031) were also noted. CONCLUSION: Skull base osteosarcomas present management challenges in which both local and systemic disease progression is the cause of mortality. Achieving R0 resections significantly improves PFS and DSS in treatment-naïve patients within multimodality treatment paradigms. Salvage surgery may benefit in patients after failing previous radiation and chemotherapy treatments. Further work is needed to determine optimal treatment strategies. These data represent the largest series reported to date.